Treatment of degenerative massive rotator cuff tears: a study protocol for a randomized non-inferiority comparative surgical trial - Alexandre Lädermann; Anthony Pernoud; Blaise Cochard; Hugo Bothorel (Trials)
Abstract Background Massive degenerative rotator cuff tears (MRCTs) represent a persistent challenge in shoulder surgery. While arthroscopic rotator cuff repair (ARCR) remains a widely accepted treatment with good functional outcomes, it is associated with a risk of retear and progression to cuff tear arthropathy. Reverse shoulder arthroplasty (RSA) has emerged as a viable alternative, particularly in cases where the reparability of the cuff is uncertain, offering pain relief and functional improvement. However, the optimal treatment approach for repairable MRCT in patients aged 60 to 80 years remains debated. This trial aims to assess whether RSA provides non-inferior outcomes to ARCR in patients with degenerative MRCTs, with a particular focus on function, pain, and quality of life. Methods This is a prospective, randomized, controlled, non-inferiority trial. A total of 145 patients with symptomatic, repairable MRCT will be enrolled and randomized in a 1:1 ratio to undergo either ARCR or RSA. The primary outcome is the American Shoulder and Elbow Surgeons (ASES) score at 24 months postoperatively. Secondary outcomes include ASES at 6 weeks and 6 months; Visual Analog Scale (VAS) for pain; Single Assessment Numeric Evaluation (SANE); Constant score; range of motion (ROM) in flexion, extension, and internal/external rotation; repair integrity (ultrasound for ARCR, radiographs for RSA); and complication rates. PROMs will be assessed at baseline, 1.5, 6, and 24 months. All adverse events and complications will be systematically recorded. Discussion This trial will provide robust comparative data to assess whether RSA is non-inferior to ARCR at two years postoperatively in terms of shoulder function and patient-reported outcomes in patients with repairable MRCT. The results aim to support evidence-based decision-making in clinical practice. Trial registration The protocol was approved by the Ethics Committee Board (CCER 2023–00111) in March 2023 and by ClinicalTrial.gov (NCT05807854).